Effect of yelling on maximal aerobic power during an incremental test of cycling performance - Chien-Liang Chen; Nan-Ying Yu; Jing-Shia Tang; Shao-Hsia Chang; Yea-Ru Yang; Lin Wang (Elsevier, 2016)
Background: People experiencing strong feelings of fatigue during exercise sometimes subconsciously yell to refocus their efforts and, thus, maintain exercise performance. The present study examined the influence of yelling during high-intensity exercise by analysing cardiorespiratory reactions and integrated electromyography (iEMG) changes in the vastus lateralis during a cycle ergometer test. Methods: A total of 23 moderately trained people were recruited. The cycling test began with a resistance of 25 W/min, which was gradually increased. During the experimental trial, the participants were required to yell at least 3 times when they felt exhausted; during the controlled trial, they were not allowed to produce any yelling sounds. The testing order was randomly assigned and the 2 trials were completed within an interval between 3-10 days. Two-way repeated measures ANOVA was applied to analyse the differences within and between the trials, and interaction of trial and time. Results: The peak power and time to exhaustion (p < 0.01) in the yelling trial were higher than those in the control trial. However, the vastus lateralis iEMG values of both trials at peak power were not significantly different. During the yelling period at 90%-100% of the maximal effort, a significant time-by-trial interaction (p < 0.05) was observed in oxygen consumption (VO2), CO2 production, O2 pulse, ventilation, and respiratory rate. All the above measures showed a significant between-trial difference (p < 0.02). However, heart rate, respiratory exchange ratio, end-tidal oxygen pressure, and ventilatory equivalent for oxygen showed only significant between-trial difference (p < 0.05), but without interaction of trial and time. Conclusion: Yelling enhances the peak O2 pulse and VO2 and maintains CO2-exclusion efficiency during high-intensity exercise. It may enable maintaining muscle activation without stronger EMG signals being required during high-intensity exercise. Keywords: Aerobic exercise, Cardiopulmonary exercise test, Intense exercise, Performance-enhancing effect, Respiratory-cardiac activities, Shouting